Method for synthesizing hierarchical pore ETS-10 zeolite without template agent or additive

By using water glass and raw materials such as alkyl titanate to perform hydrothermal crystallization reaction without template agents or additives, ETS-10 zeolite molecular sieve with multi-stage pore structure and high crystallinity was successfully synthesized, which solved the problems of high cost and environmental pollution in traditional methods and achieved green and environmentally friendly and efficient synthesis.

CN119706858AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311255157.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The prior art is difficult to synthesize high crystallinity ETS-10 zeolite molecular sieve with multi-stage pore structure without template agents or additives, and traditional methods have problems with high costs, environmental pollution and impurities in products.

Method used

Water glass is used as the silicon source, alkyl titanate is used as the titanium source, KCl and KOH are used as the potassium source, and sodium salt complexing agents are used as the sodium source. Multi-stage pore ETS-10 zeolite molecular sieve is synthesized through hydrothermal crystallization reaction without template agents or additives.

Benefits of technology

The ETS-10 zeolite molecular sieve with multi-stage pore structure and high crystallinity can be synthesized without template agents or additives, reducing production costs, and the method is green and environmentally friendly and avoiding environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706858A_ABST
    Figure CN119706858A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing hierarchical porous ETS-10 zeolite without a template agent or an additive. The method comprises the following steps: taking water glass as a silicon source, alkyl titanate as a titanium source, KCl and KOH as potassium sources and a sodium salt complexing agent as a sodium source; the preparation method comprises the following steps: adding alkyl titanate into a water glass solution, then adding a sodium salt complexing agent solution, finally adding KCl and KOH solutions, adjusting the pH value to 11, uniformly stirring, carrying out a hydrothermal crystallization reaction, taking out a product, washing, drying and calcining to obtain the hierarchical porous ETS-10 zeolite molecular sieve. The prepared ETS-10 zeolite has a hierarchical pore structure, the specific surface area is 262-334 m < 2 > / g, and the mesoporous volume is 0.05-0.14 cm < 3 > / g. According to the method disclosed by the invention, a mesoporous template agent and an additive are not needed, and the synthesized hierarchical pore ETS-10 zeolite has relatively high crystallinity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zeolite molecular sieve synthesis, and in particular relates to a method for synthesizing multi-level pore ETS-10 zeolite without a template or additive. Background Art

[0002] Zeolites with high specific surface area and tunable acid / base sites are considered as potential candidates for catalyzing the direct carbonylation of glycerol with CO2. In particular, titanosilicate zeolite ETS-10, as a zeolite with intrinsic Lewis base sites, has been shown to effectively adsorb and activate CO2 due to its unique framework and chemical composition, but its microporous nature will cause severe mass transfer limitations, which inevitably hinders their practical application in macromolecular reactions.

[0003] The introduction of multi-level pores can change the morphology and some physical and chemical properties of zeolites, reduce the length of the diffusion path, improve the diffusion capacity, and maximize the structural function in a limited space, thereby improving the mass transfer efficiency. Therefore, the design and synthesis of multi-level pore molecular sieves are considered to have great industrial application prospects and have played an important role in many catalytic reactions such as alkylation, acylation, Fischer-Tropsch synthesis, hydrogenation conversion, and biomass conversion. The introduction of the multi-level pore structure of ETS-10 zeolite molecular sieve was initially achieved through acid and alkali post-treatment or microwave radiation-assisted methods. The porosity was limited, and the pore structure of the zeolite was also damaged to a certain extent.

[0004] Recently, the use of organic templates or additives such as long-chain aminosilanes, sodium lignosulfonate, metal nitrates, etc. has been reported to successfully synthesize hierarchical pore ETS-10 zeolite molecular sieves. However, this method easily leads to the formation of impurities such as ETS-4, AM-1, AM-2, AM-3 and AM-4. In addition, the synthesis process of the template itself is complicated, expensive, and will cause serious environmental pollution. This not only greatly increases the production cost of the zeolite, but also does not conform to the current social trend of low-carbon sustainable development.

[0005] US4853202 and US4938939 disclose that ETS-10 zeolite molecular sieve can be synthesized in the absence of an organic template, but it requires the presence of a large amount of fluoride ions and the use of TiO2, TiCl3, TiCl4, TiF4, etc. as a titanium source.

[0006] In order to obtain high-purity and high-crystallinity ETS-10, in addition to fluoride ions, US5453263 discloses that a certain amount of seed crystals can also be added.

[0007] Research reports that ETS-10 was synthesized using Ti2(SO4)3, TiCl3, and TiO2 as titanium sources without adding fluoride ions, organic templates, and seed crystals. However, under these conditions, the product contained titanium dioxide impurities (Micropor. Mesopor. Mater., 2004, 67, 181).

[0008] Therefore, there is still a need to continue to develop a simple and effective method for directly synthesizing a high-crystallinity ETS-10 zeolite molecular sieve with a multi-level pore structure without using a template or additive. Summary of the invention

[0009] Purpose of the invention: The purpose of the present invention is to provide a method for synthesizing hierarchical pore ETS-10 zeolite without template or additive. The synthesis method of the present invention is simple, safe, low-cost, and environmentally friendly.

[0010] How to synthesize a high-crystallinity ETS-10 zeolite molecular sieve with a multi-level pore structure without a template or additive is a key technical problem to be solved by the present invention. The present invention provides a method for synthesizing a multi-level pore ETS-10 zeolite molecular sieve, and the synthesized ETS-10 zeolite molecular sieve has a multi-level pore structure and a high crystallinity.

[0011] Technical solution: The purpose of the present invention is achieved through the following technical solution:

[0012] The present invention provides a method for synthesizing hierarchical pore ETS-10 zeolite without template or additive, comprising the following steps:

[0013] Using water glass as a silicon source, alkyl titanate as a titanium source, KCl and KOH as potassium sources, and a sodium salt complexing agent as a sodium source; adding the alkyl titanate into the water glass solution, then adding the sodium salt complexing agent solution, and finally adding the KCl and KOH solutions, adjusting the pH to 11, stirring evenly, and then performing a hydrothermal crystallization reaction, taking out the product, washing, drying, and calcining, to obtain a multi-level pore ETS-10 zeolite molecular sieve.

[0014] Preferably, the alkyl titanate is one of tetra-n-butyl titanate, tetra-isooctyl titanate, tetra(2-ethylhexyl) orthotitanate, tetra(octadecyl) orthotitanate, isopropyl triisostearate titanate, butyl phosphate titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate or bis(acetylacetonato)isobutoxyisopropoxy titanate.

[0015] Preferably, the sodium salt complexing agent is one of disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium oxalate, sodium acetate, pentasodium diethylenetriaminepentaacetate, sodium tartrate or sodium citrate.

[0016] In a specific embodiment of the present invention, tetra(octadecyl)orthotitanate is used as a titanium source and sodium citrate is used as a sodium source. The different coordination effects between tetra(octadecyl)orthotitanate and sodium citrate play a key role in adjusting the pore size of the multi-level pore ETS-10, so that the mesopore size can be adjusted by changing the molar ratio of the titanium source to the sodium source.

[0017] Preferably, the modulus of the water glass is 2.3-3.4, and the SiO2 concentration in the solution is 5.90-7.55 mol / L.

[0018] The water glass in the present invention is a sodium silicate aqueous solution (Na2O·n SiO2), where n is the modulus. The water glasses of several moduli described in the present invention are all commonly used moduli in industry.

[0019] Preferably, the reaction temperature of the crystallization reaction is 180-240° C., and the reaction time is 48-80 h.

[0020] Preferably, the molar ratio of each raw material in the system is added according to SiO2:TiO2:K2O:Na2O:H2O=(6.4-7.0):1.0:(1.6-2.0):(3.4-4.0):(157-168).

[0021] The molar number of Na2O is calculated as the sum of the sodium elements contained in the water glass and the sodium salt complexing agent, and the molar number of K2O is calculated as the sum of the potassium elements contained in KCl and KOH. The present invention provides the content of SiO2 in the water glass and the modulus of the water glass, and the content of Na2O can be calculated from them.

[0022] Preferably, the calcination method is calcination at 450° C. for 6 hours.

[0023] The present invention also provides the multi-level porous ETS-10 zeolite synthesized by the method for synthesizing the multi-level porous ETS-10 zeolite without a template or an additive.

[0024] Preferably, the crystallinity of the hierarchical pore ETS-10 zeolite is ≥ 80%.

[0025] Furthermore, the crystallinity of the multi-level pore ETS-10 zeolite is ≥93%.

[0026] Preferably, the specific surface area of ​​the ETS-10 zeolite is 262-334 m2 / g, and the mesopore volume is 0.05-0.14 cm 3 / g.

[0027] Beneficial effects:

[0028] (1) The present invention does not use a template or additive, but uses inexpensive water glass as a silicon source, an alkyl titanate as a titanium source, and a sodium salt complexing agent as a sodium source, and directly synthesizes a high-crystallinity ETS-10 zeolite molecular sieve with a multi-level pore structure through hydrothermal crystallization. The synthesis method of the present invention is simple, safe, low-cost, and environmentally friendly.

[0029] (2) In the synthesis process of the present invention, the different coordination effects between the alkyl titanate and the sodium salt complexing agent play a key role in adjusting the pore size of the multi-level pore ETS-10, so that the mesoporous pore size can be adjusted by changing the amount of titanium source and sodium source in the synthesis system. Compared with the prior art, the dependence on mesoporous organic templates or additives in the traditional synthesis method is greatly reduced, providing a simple and environmentally friendly method for synthesizing ETS-10 zeolite molecular sieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 XRD patterns of hierarchical pore ETS-10 zeolite molecular sieves synthesized with different silicon-titanium ratios; a represents SiO2:TiO2=6.0, b represents SiO2:TiO2=6.4, c represents SiO2:TiO2=6.8, d represents SiO2:TiO2=7.0, and e represents SiO2:TiO2=7.2.

[0031] Figure 2 XRD patterns of hierarchical pore ETS-10 zeolite molecular sieves synthesized with different potassium-titanium ratios; a represents K2O:TiO2=0.8, b represents K2O:TiO2=1.2, c represents K2O:TiO2=1.6, d represents K2O:TiO2=2.0, and e represents K2O:TiO2=2.2.

[0032] Figure 3 XRD patterns of hierarchical pore ETS-10 zeolite molecular sieves synthesized with different water-titanium ratios; a represents H2O:TiO2=150, b represents H2O:TiO2=157, c represents H2O:TiO2=163, d represents H2O:TiO2=168, e represents H2O:TiO2=175, and f represents H2O:TiO2=180.

[0033] Figure 4 XRD patterns of hierarchical pore ETS-10 zeolite molecular sieves synthesized with different sodium-titanium ratios; a represents Na2O:TiO2=3.2, b represents Na2O:TiO2=3.6, c represents Na2O:TiO2=3.8, d represents Na2O:TiO2=4.0, and e represents Na2O:TiO2=4.2.

[0034] Figure 5XRD patterns of hierarchical pore ETS-10 zeolite molecular sieves synthesized with different additives; wherein a represents comparative example 11, b represents comparative example 12, c represents comparative example 13, and d represents comparative example 14. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0036] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0037] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements proposed by relevant enterprises. Unless otherwise specified, all parts are by weight and all percentages are by weight.

[0038] In the following examples and comparative examples, in the expression of the molar ratio of each material "SiO2: TiO2: K2O: Na2O: H2O", SiO2 refers to the silicon source, and the molar number of the silicon source is the molar number of the silicon element in the water glass; TiO2 refers to the titanium source, and the molar number of the titanium source is the molar number of the titanium element in the alkyl titanate or titanium trichloride; K2O refers to the potassium source, and the molar number of the potassium source is the molar number of the potassium element in KCl and KOH; Na2O refers to the sodium source, and the molar number of the sodium source is the sum of the molar numbers of the sodium element in the system derived from the water glass, the sodium salt complexing agent, and the sodium hydroxide; H2O refers to the water source, and the molar number of the water source is the sum of the water contained in the system derived from the water glass and other solutions. The composition of the water glass is: SiO2: 5.90-7.55 mol / L, modulus n: 2.3-3.4.

[0039] Test and calculation method of crystallinity (%): The crystallinity is tested using an X-ray diffractometer, and the calculation formula is: crystallinity = (diffraction peak intensity / total intensity) * 100%, and jade software is used for data processing.

[0040] S BET The nitrogen adsorption was measured using a physical adsorption instrument.

[0041] Example 1

[0042] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0043] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0044] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.2, SiO2 concentration 6.8mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 200℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0045] Example 2

[0046] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0047] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0048] 9.0g of tetra(octadecyl) orthotitanate was added to 8.8mL of water glass (modulus 3.2, SiO2 concentration 6.8mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 200℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 6.8: 1.0: 2.0: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0049] Example 3

[0050] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0051] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0052] 9.0g of tetra(octadecyl) orthotitanate was added to 8.4mL of water glass (modulus 3.2, SiO2 concentration 6.8mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 200℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 6.4: 1.0: 2.0: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0053] Comparative Example 1

[0054] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0055] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0056] 9.0g of tetra(octadecyl) orthotitanate was added to 9.4mL of water glass (modulus 3.2, SiO2 concentration 6.8mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, stirred for another 60min, and the obtained mixture was put into a high pressure reactor and placed in a 200℃ oven for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.2: 1.0: 2.0: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0057] Comparative Example 2

[0058] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0059] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0060] 9.0g of tetra(octadecyl) orthotitanate was added to 7.9mL of water glass (modulus 3.2, SiO2 concentration 6.8mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 200℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 6.0: 1.0: 2.0: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0061] The purpose of setting up Experimental Examples 1-3 and Comparative Examples 1-2 is to compare the effects of different silicon-titanium ratio systems. The ETS-10 zeolite prepared in Experimental Examples 1-3 and Comparative Examples 1-2 was subjected to XRD testing. The obtained XRD patterns are shown in Figure 1 .

[0062] It can be seen from the crystallinity, mesopore volume and XRD spectrum in Table 1 that multi-level pore ETS-10 zeolite can be synthesized when the silicon-titanium ratio is between 6.4 and 7.0. When the silicon-titanium ratio is lower than 6.4, a large number of impurity peaks appear, the crystallinity is significantly lowered, and a large amount of precipitation gradually appears during the synthesis process. This is because when the silicon-titanium ratio in the system decreases, the content of the corresponding silicon species decreases and the pH of the system decreases. When its content is not enough to combine with the quantitative inorganic titanium species in the system to form titanosilicate, the synthetic precursor cannot further grow into an ETS-10 zeolite nucleus. When the silicon-titanium ratio is higher than 7.0, the XRD spectrum of the sample shows a typical quartz peak at 2θ=27°. The reason for this phenomenon is that the increase in Si / Ti causes SiO2 in the system to polymerize to form quartz. Therefore, the silicon-titanium ratio of 7.0 in Example 1 is the best ratio.

[0063] Example 4

[0064] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0065] Solution B: Prepare by dissolving 0.7 g KOH and 0.98 g KCl in 5 mL H2O.

[0066] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 1.6: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0067] Comparative Example 3

[0068] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0069] Solution B: Prepare by dissolving 0.7 g KOH and 1.7 g KCl in 5 mL H2O.

[0070] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.2: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0071] Comparative Example 4

[0072] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0073] Solution B: Prepare by dissolving 0.7 g KOH and 0.5 g KCl in 5 mL H2O.

[0074] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system was SiO2: TiO2: K2O: Na2O: H2O was recorded as 7.0: 1.0: 1.2: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0075] Comparative Example 5

[0076] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0077] Solution B: Prepare by dissolving 0.7 g KOH in 5 mL H2O.

[0078] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 0.8: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0079] Experimental Example 4 and Comparative Examples 3-5 are designed to compare the effects of different potassium-titanium ratio systems. The ETS-10 zeolite prepared in Examples 1 and 4 and Comparative Examples 3-5 is subjected to XRD testing. The obtained XRD patterns are shown in Figure 2 .

[0080] From the crystallinity, mesopore volume and XRD spectrum in Table 1, we can see that the multi-level pore ETS-10 zeolite can be synthesized when the potassium-titanium ratio is between 1.6 and 2.0. When the potassium-titanium ratio is lower than 1.6, not only the crystallinity is greatly reduced, but also a large amount of AM-3 impurities appear. This is because K is required in the ETS-10 zeolite synthesis system. + The ions act as structure directors and guide the transformation of amorphous silicates and titanium species into crystals. + As a bridging medium during the synthesis process, K is required to promote silicate polymerization to form a dense gel.+ The larger ionic radius is used to hinder the aggregation of silicate anions. When the potassium-titanium ratio is higher than 2.0, ETS-10 zeolite cannot be synthesized. This is because there is an excess of K with a larger ionic radius in the system. + It is also easy to cause the molecular sieve pores to be blocked. Therefore, the potassium-titanium ratio in Example 1 is 2.0, which is the best ratio.

[0081] Example 5

[0082] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0083] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 7.0 mL H2O.

[0084] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 4.0: 168. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0085] Example 6

[0086] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0087] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5.5 mL H2O.

[0088] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system was SiO2: TiO2: K2O: Na2O: H2O was recorded as 7.0: 1.0: 2.0: 4.0: 157. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0089] Comparative Example 6

[0090] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0091] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 8.8 mL H2O.

[0092] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system, SiO2: TiO2: K2O: Na2O: H2O, was recorded as 7.0: 1.0: 2.0: 4.0: 180. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0093] Comparative Example 7

[0094] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0095] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 8.0 mL H2O.

[0096] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system was SiO2: TiO2: K2O: Na2O: H2O was recorded as 7.0: 1.0: 2.0: 4.0: 175. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0097] Comparative Example 8

[0098] Solution A: Prepare by dissolving 7.38 g of sodium citrate in 10 mL of H2O.

[0099] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 4.5 mL H2O.

[0100] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 230℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is 7.0:1.0:2.0:4.0:150. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0101] Experimental Examples 5-6 and Comparative Examples 6-8 are designed to compare the effects of different water-titanium ratio systems. XRD tests were performed on the ETS-10 zeolites prepared in Examples 1, 5 and 6 and Comparative Examples 6-8. The obtained XRD patterns are shown in Figure 3 .

[0102] From the crystallinity, mesopore volume and XRD spectrum in Table 1, we can see that the multi-level pore ETS-10 zeolite can be synthesized when the water-titanium ratio is between 157-168. When the water-titanium ratio is high or low, more impurity peaks will appear in the synthesized samples. The amount of water will affect the viscosity of the system. When the viscosity increases, the intermolecular force will increase, which is conducive to the formation of the ETS-10 zeolite molecular sieve framework. When the viscosity increases to a certain extent, it is not conducive to stirring, resulting in uneven mixing of the inorganic species in the system, which is not conducive to the growth and formation of ETS-10 crystals and will induce the formation of impurities.

[0103] Example 7

[0104] Solution A: Prepare by dissolving 5.92 g of sodium citrate in 10 mL of H2O.

[0105] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0106] 9.0g of tetra(octadecyl) orthotitanate was added to 7.2mL of water glass (modulus 2.3, SiO2 concentration 7.55mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 180℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 3.4: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0107] Example 8

[0108] Solution A: Prepare by dissolving 6.69 g of sodium citrate in 10 mL of H2O.

[0109] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0110] 9.0g of tetra(octadecyl) orthotitanate was added to 7.2mL of water glass (modulus 2.3, SiO2 concentration 7.55mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 180℃ for hydrothermal crystallization for 80h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 3.8: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0111] Example 9

[0112] Solution A: Prepare by dissolving 5.74 g of sodium citrate in 10 mL of H2O.

[0113] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0114] 9.0g of tetra(octadecyl) orthotitanate was added to 7.2mL of water glass (modulus 2.3, SiO2 concentration 7.55mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, stirred for another 60min, and the obtained mixture was put into a high pressure reactor and placed in an oven at 180℃ for hydrothermal crystallization for 80h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 3.6: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0115] Comparative Example 9

[0116] Solution A: Prepare by dissolving 8.21 g of sodium citrate in 10 mL of H2O.

[0117] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0118] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 180℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 4.2: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0119] Comparative Example 10

[0120] Solution A: Prepare by dissolving 4.10 g of sodium citrate in 10 mL of H2O.

[0121] Solution B: Prepare by dissolving 0.7 g KOH and 1.45 g KCl in 5 mL H2O.

[0122] 9.0g of tetra(octadecyl) orthotitanate was added to 7.2mL of water glass (modulus 2.3, SiO2 concentration 7.55mol / L), stirred for 30min, then solution A was added, stirred for 60min, and finally solution B was added, pH was adjusted to about 11, and stirred for another 60min. The obtained mixture was put into a high pressure reactor and placed in an oven at 180℃ for hydrothermal crystallization for 80h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 3.2: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 1.

[0123] Experimental Examples 7-9 and Comparative Examples 9-10 are designed to compare the effects of different amounts of sodium citrate on the system. The ETS-10 zeolite prepared in Examples 1, 7-9 and Comparative Examples 9-10 was subjected to XRD testing and BET characterization. The obtained XRD patterns are shown in Figure 4 .

[0124] From the crystallinity, mesopore volume and XRD spectrum in Table 1, we can see that the molar ratio of sodium citrate to titanium can be between 3.4 and 4.0 to synthesize hierarchical ETS-10 zeolite, and the ETS-10 synthesized below 3.4 or above 4.0 has anatase and quartz impurities. Examples 1, 7, 8, and 9 can all synthesize hierarchical ETS-10 zeolite, and the best crystallinity is achieved when the molar ratio of sodium citrate to titanium is 3.6. Therefore, the molar ratio of sodium citrate to titanium in Example 9 is 3.6, which is the best ratio.

[0125] Table 1 Preparation parameters and texture properties of products

[0126]

[0127] Example 10

[0128] Solution A: Prepare by dissolving 5.74 g of sodium citrate in 10 mL of H2O.

[0129] Solution B: Prepare by dissolving 0.3 g KOH and 2.0 g KCl in 5 mL H2O.

[0130] 15.9g of tetraisooctyl titanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was slowly added dropwise, stirred for 60min, solution B was added, stirred for another 60min, pH was adjusted to about 11, the obtained mixture was put into a high pressure reactor, placed in an oven at 240℃ for hydrothermal crystallization for 72h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system, SiO2: TiO2: K2O: Na2O: H2O, was recorded as 7.0: 1.0: 2.0: 3.6: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 2.

[0131] Embodiment 11

[0132] Solution A: Prepare by dissolving 3.6 g of sodium oxalate in 10 mL of H2O.

[0133] Solution B: Prepare by dissolving 0.3 g KOH and 2.0 g KCl in 5 mL H2O.

[0134] 9.0g of tetra(octadecyl) orthotitanate was added to 9.2mL of water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 30min, then solution A was slowly added dropwise, stirred for 60min, solution B was added, stirred for another 60min, pH was adjusted to about 11, the obtained mixture was put into a high pressure reactor, placed in an oven at 240℃ for hydrothermal crystallization for 64h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 3.6: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 2.

[0135] Table 2 Textural properties of molecular sieves prepared from different titanium and sodium sources

[0136]

[0137] Comparative Example 11 Preparation of Traditional Microporous ETS-10 Zeolite Molecular Sieve

[0138] 1.8g potassium fluoride was dissolved in 5mL H2O to form solution A; 1.45g sodium hydroxide was dissolved in 10mL water and added dropwise to 9.2mL water glass (modulus 3.4, SiO2 concentration 5.9mol / L), stirred for 10min and then 5.9g TiCl3 was added dropwise, stirred for 60min and then solution A was added dropwise; after stirring for 2h, the mixture was placed in a hydrothermal reactor and sealed, and crystallized in an oven at 230℃ for 72h. The molar ratio of each material in the system, SiO2: TiO2: K2O: Na2O: H2O, was recorded as 7.0: 1.0: 1.9: 4.0: 163. The texture properties of the prepared microporous ETS-10 are shown in Table 3.

[0139] Comparative Example 12 Preparation of traditional multi-level pore ETS-10 zeolite molecular sieve

[0140] The preparation of hierarchical ETS-10 zeolite using a soft template method has been reported in relevant patents and literature, using N, N-diethyl-N-hexadecyl-N-(3-methoxysilane propane) ammonium iodide (DMMC) or N, N-diethyl-N-octadecyl-N-(3-methoxysilane propane) ammonium bromide (TPOAB) as a template. For this purpose, we will use DMMC and TPOAB as soft templates to synthesize hierarchical ETS-10, and the preparation method is as follows: 1.8g potassium fluoride is dissolved in 5mL H2O to form solution A; 1.45g sodium hydroxide is dissolved in 10mL water and added dropwise to 9.2mL water glass (modulus of 3.4, SiO2 concentration of 5.9mol / L), and 5.9g TiCl3 is added dropwise after stirring for 10min, and solution A is added dropwise after stirring for 60min; after stirring for 2h, 4.0mL TPOAB or 2.5mL DMMC is added. Then it was placed in a hydrothermal reactor, sealed, and crystallized in an oven at 230°C for 72 hours. The molar ratio of each material in the system, SiO2: TiO2: K2O: Na2O: H2O, was recorded as 7.0: 1.0: 1.9: 4.0: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 3.

[0141] Comparative Example 13 Preparation process of traditional TiCl3 as titanium source and sodium citrate as sodium source

[0142] Solution A: Prepare by dissolving 5.74 g of sodium citrate in 10 mL of H2O.

[0143] Solution B: Prepared by dissolving 1.4 g KOH and 0.52 g KCl in 5 mL H2O.

[0144] Solution B was added dropwise to 9.2 mL of water glass (modulus 2.3, SiO2 concentration 7.55 mol / L), stirred for 30 min, then 7.3 g of TiCl3 solution was slowly added, stirred for 60 min, solution A was added, pH was adjusted to about 11, stirred for another 60 min, the obtained mixture was loaded into a high pressure reactor, placed in an oven at 240 ° C for hydrothermal crystallization for 48 h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450 ° C for 6 h. The molar ratio of each material in the system was SiO2: TiO2: K2O: Na2O: H2O was recorded as 7.0: 1.0: 2.0: 3.60: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 3.

[0145] Comparative Example 14 Preparation process of tetra(octadecyl) orthotitanate as titanium source and NaCl as sodium source

[0146] Solution A: Prepare by dissolving 1.32 g NaCl in 10 mL H2O.

[0147] Solution B: Prepare by dissolving 0.3 g KOH and 2.0 g KCl in 5 mL H2O.

[0148] 9.0g of tetra(octadecyl) orthotitanate was added to 7.2mL of water glass (modulus 2.3, SiO2 concentration 7.55mol / L), stirred for 30min, then solution A was slowly added dropwise, stirred for 60min, solution B was added, stirred for another 60min, pH was adjusted to about 11, the obtained mixture was put into a high pressure reactor, placed in an oven at 240℃ for hydrothermal crystallization for 48h; the product obtained by the reaction was filtered, washed, dried, and calcined at 450℃ for 6h. The molar ratio of each material in the system is SiO2: TiO2: K2O: Na2O: H2O is recorded as 7.0: 1.0: 2.0: 3.6: 163. The texture properties of the obtained multi-level porous ETS-10 are shown in Table 3.

[0149] like Figure 5 As shown, ETS-10 zeolite molecular sieves can be synthesized in Comparative Examples 11-14. In Comparative Example 12, a commonly used organic template was used to successfully synthesize an ETS-10 zeolite molecular sieve with a mesoporous pore volume, but the crystallinity was poor, while in Example 9, the multi-level pore ETS-10 synthesized by the organic template-free method had a higher crystallinity. In addition, in Comparative Examples 13 and 14, only microporous ETS-10 zeolite molecular sieves can be synthesized when only commonly used TiCl3 is used as a titanium source, or when NaCl is used as a sodium source, which indicates that alkyl titanate and sodium citrate are essential in the mesopore generation process.

[0150] Table 3 Texture properties of hierarchical ETS-10 synthesized by different methods and additives

[0151]

[0152] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A method for synthesizing hierarchical pore ETS-10 zeolite without template or additive, characterized in that: The steps include: Using water glass as a silicon source, alkyl titanate as a titanium source, KCl and KOH as potassium sources, and a sodium salt complexing agent as a sodium source; adding the alkyl titanate into the water glass solution, then adding the sodium salt complexing agent solution, and finally adding the KCl and KOH solutions, adjusting the pH to 11, stirring evenly, and then performing a hydrothermal crystallization reaction, taking out the product, washing, drying, and calcining, to obtain a multi-level pore ETS-10 zeolite molecular sieve.

2. The method for synthesizing hierarchical pore ETS-10 zeolite without template or additive according to claim 1, characterized in that: The alkyl titanate is one of tetra-n-butyl titanate, tetra-isooctyl titanate, tetra(2-ethylhexyl) orthotitanate, tetra(octadecyl) orthotitanate, isopropyl triisostearate titanate, butyl phosphate titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate or bis(acetylacetonato)isobutoxyisopropoxy titanate.

3. The method for synthesizing hierarchical pore ETS-10 zeolite without template or additive according to claim 1, characterized in that: The sodium salt complexing agent is one of disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium oxalate, sodium acetate, pentasodium diethylenetriaminepentaacetate, sodium tartrate or sodium citrate.

4. The method for synthesizing hierarchical pore ETS-10 zeolite without template or additive according to claim 1, characterized in that: The modulus of the water glass is 2.3-3.4, and the SiO2 concentration in the solution is 5.90-7.55 mol / L.

5. The method for synthesizing hierarchical pore ETS-10 zeolite without template or additive according to claim 1, characterized in that: The reaction temperature of the crystallization reaction is 180-240° C., and the reaction time is 48-80 hours.

6. The method for synthesizing hierarchical pore ETS-10 zeolite without template or additive according to claim 1, characterized in that: The molar ratio of each raw material in the system is SiO2:TiO2:K2O:Na2O:H2O=(6.4-7.0):1.0:(1.6-2.0):(3.4-4.0):(157-168), wherein the molar number of Na2O is calculated as the sum of the sodium elements contained in water glass and the sodium salt complexing agent, and the molar number of K2O is calculated as the sum of the potassium elements contained in KCl and KOH.

7. The method for synthesizing hierarchical pore ETS-10 zeolite without template or additive according to claim 1, characterized in that: The calcination method is calcination at 450° C. for 6 hours.

8. The multi-level porous ETS-10 zeolite synthesized by the method for synthesizing the multi-level porous ETS-10 zeolite without a template or an additive as claimed in any one of claims 1 to 7.

9. The multi-level pore ETS-10 zeolite according to claim 8, characterized in that: The crystallinity of the multi-level pore ETS-10 zeolite is ≥80%.

10. The multi-level pore ETS-10 zeolite according to claim 8, characterized in that: The specific surface area of ​​the ETS-10 zeolite is 262-334 m 2 / g, and the mesopore volume is 0.05-0.14cm 3 / g.

Citation Information

Patent Citations

  • Desulfurization adsorbent for fuel cell and desulfurizing method using the same

    CN101168692A

  • Synthesis method for synthesizing mesoporous ETS-10 zeolite containing metal from template-free agent

    CN109264738A

  • Synthesis method of high-crystallinity ETS-10 zeolite molecular sieve with adjustable morphology and adjustable pore structure

    CN110562993A

  • Hierarchical-pore ETS-10 zeolite molecular sieve with specific molecular recognition function and synthesis method thereof

    CN110577228A

  • Titanium silicalite molecular sieve, preparation method thereof and method for producing ketoxime through ammoximation reaction of macromolecular ketones

    CN112744838A